Reaffirmation of Student Religiosity through Religion Teacher Strategies: An Exploratory Study in the Era of Globalization - Husniyatus Salamah Zainiyati; Suryani Suryani; Abdul Rahim Karim (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
This study aims to reveal the strategy of religious teachers in strengthening students' religiosity in the era of globalization. To answer this research problem, a qualitative approach is used with the type of literature study. Data collection is done by finding sources and constructing from various sources such as journals and research that has been done. At a later stage, data processing and/ or quoting references are carried out to be displayed as research findings, abstracted to obtain complete information, and interpreted to produce knowledge to conclude. The results of this study show the fragility of the religiosity of students in the era of globalization, the factors that cause the fragility of the religiosity of students in the era of globalization, the solution strategy of religious teachers to strengthen the religiosity of students in the era of globalization, and the constancy of the religiosity of students in the era of globalization by making religious teachers as driving teachers.